"Living on the edge": Estimating the economic cost of sea level rise on coastal real estate in the Tampa Bay region, Florida. (December 2016) - Fu, Xinyu; Song, Jie; Sun, Bowen; Peng, Zhong-Ren
Abstract: Climate change and especially sea level rise are posing unprecedented pressure on coastal communities through enhanced coastal flooding and saltwater intrusion. Thus, adapting to its impacts has drawn global attention. Since the cost-efficiency of adaptation alternatives is crucial in decision making, accurately estimating the economic cost of sea level rise is an imperative task for coastal planners and managers. This study employed a spatial hedonic approach to estimate the economic cost due to inundation by future sea level rise. The applied methodology provides better estimates of the economic losses due to sea level rise by accounting for lost coastal amenities, and the results generated can also be utilized for cost-benefit analysis. In 2050, it is estimated that the inundation of 3-foot sea level rise could cost Hillsborough and Pinellas County over 300 and 900 million dollars respectively for the real estate market alone. Local coastal planners and managers may find this methodology useful in estimating the potential economic cost due to sea level rise and support making adaptation decisions. We also stressed the importance of such studies to support local decision making and enhance adaptation planning for the climate change and sea level rise in the coastal communities. Highlights: Building spatial hedonic models to estimate the factors affecting real estate values. To estimate the cost of sea level by accounting for the losing coastal amenities. Conducting a case study on sea level rise impacts in a highly vulnerable region in Florida, USA. This study stressed the importance for economic analysis in adaptation decisions.